Efficacy and Safety of Levonadifloxacin in the Management of Community-Acquired Bacterial Pneumonia (CABP): Findings of a Retrospective, Real-World, Multi-centre Study - Prabhudesai, Dr. Prahlad; Jain, Dr. Ashish; Borade, Dr. Prashant; Khandelwal, Dr. Abhijeet; Mehta, Kapil; Bhapkar, Dr. Sandeep; Thampi, Dr. Bini; Sonone, Dr. Pramit (International Journal of Innovative Research in Medical Science, 2021)
Background: Community-acquired bacterial pneumonia (CABP) remains a global public health threat and is a leading cause of hospitalization and infection-linked mortality. Levonadifloxacin is a novel benzoquinolizine antibiotic with a broad-spectrum activity including methicillin-resistant Staphylococcus aureus (MRSA) and CABP-pathogens. Methods: This multi-centre, retrospective, post-marketing, real-world study assessed the efficacy and safety of levonadifloxacin oral and/or intravenous therapy in the treatment of CABP. Data from 338 patients above 17 years-of-age who received levonadifloxacin (oral or intravenous or both) was collected from 89 healthcare facilities across India. Information on clinical condition, comorbidities, complications, and details of concurrent therapy (including antimicrobial agents) was also collected. Study outcomes were clinical and microbial success at the end of therapy while safety was assessed based on clinical and laboratory adverse events. Results: Of the 338 patients, 244 (72.2%) were male, 93 (27.5%) were female and 1 (0.43%) was a transgender. About 294 (87.0%) patients were hospital-treated and 44 (13%) received outpatient treatment. About 248 (73.4%) patients received intravenous levonadifloxacin treatment, 79 (23.4%) received oral and 11 (3.3%) received intravenous followed by oral levonadifloxacin therapy. The common comorbid conditions were diabetes (14.2%) and hypertension (8.6%). Mean duration of levonadifloxacin therapy was 6.4 days. Clinical and microbial success in levonadifloxacin-treated patients was 95.0% (321/388) and 96.8% (150/155), respectively. Conclusions: Levonadifloxacin showed promising clinical outcomes and safety when used as an intravenous and/or oral for the treatment of CABP, both in outpatients as well as hospitalized patients.